Drivers of the food system based on food sovereignty domains: an integrative systematic literature review - Rivera, Igor; Díaz de León, Denise; Pérez-Salazar, María del Rosario (Frontiers in Sustainable Food Systems, 2024)
Food sovereignty, as defined by the comprehensive definition offered in the 2007 Nyéléni Forum, encompasses essential action lines for transforming a food system based on food sovereignty principles. Understanding how current food system initiatives develop within these domains is crucial to identifying the processes of change needed to advance this transformation. This study aimed to summarize how advancements in food sovereignty contribute to the existing literature. To do this, a systematic literature review was conducted, analyzing 250 papers from the period 2008-2023, focusing on research methods used by the authors, food initiatives within the domains of food sovereignty, and relevant drivers of a food system based on food sovereignty domains. The results showed that approximately 36% of studies used interviews, surveys, and questionnaires for data collection, 34% focused on targeted fieldwork through case studies, about 19% utilized methods involving in-depth interaction with specific groups, and just under 10% employed document analysis methods. The most discussed domain was the use of agroecological management practices for food production, followed by the valuation of traditional knowledge, the promotion of social justice and equity, self-determination through the transformation of economic and political institutions, and the localization of food production and consumption. Food initiatives outlined broader goals within each domain of food sovereignty, with three common goals identified across domains: food security and consumption, environmental stewardship, and crisis preparedness. Twenty-nine drivers of a food system based on the domains of food sovereignty were identified, and the drivers, networks, and holistic approach were found in all five domains. Findings regarding implications for supporters of food sovereignty are described within the context of the identified goals of the food initiatives.